Optimization of Service Process in Emergency Department Using Discrete Event Simulation and Machine Learning Algorithm. - Hosseini_Shokouh, Sayyed_Morteza; Mohammadi, Kasra; Yaghoubi, Maryam (Archives of Academic Emergency Medicine, 2022)
Introduction: Emergency departments are operating with limited resources and high levels of unexpected requests. This study aimed tominimize patients' waiting time and the percentage of units' engagement to improve the emergency department (ED) efficiency. Methods: A comprehensive combination method involvingDiscrete Event Simulation (DES), Artificial Neural Network (ANN) algorithm, and finally solving the model by use of Genetic Algorithm (GA) was used in this study. After simulating the case and making sure about the validity of the model, experiments were designed to study the effects of change in individuals and equipment on the average time that patients wait, as well as units' engagement in ED. Objective functions determined using Artificial Neural Network algorithm and MATLAB software were used to train it. Finally, after estimating objective functions and adding related constraints to the problem, a fractional Genetic Algorithm was used to solve the model. Results: According to the model optimization result, it was determined that the hospitalization unit, as well as the hospitalization units' doctors, were in an optimized condition, but the triage unit, as well as the fast track units' doctors, should be optimized. After experiments in which the average waiting time in the triage section reached near zero, the average waiting time in the screening section was reduced to 158.97 minutes and also the coefficient of units' engagement in both sections were 69% and 84%, respectively. Conclusion: Using the service optimization method creates a significant improvement in patient's waiting time and stream at emergency departments, which is made possible through appropriate allocation of the human and material resources.